Management, Decision-making and Supervision of Belgian State owned Enterprises: An Inefficient Patchwork? - C. van der Elst (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2006)
In April 2005 the OECD published its guidelines on the corporate governance of state-owned enterprises (S0E). Its first guideline reads that "…SOEs should not be exempt from the application of general laws and regulations… the legal and regulatory framework should allow sufficient flexibility for adjustments in the capital structure of SOEs". In 1991, long before the corporate governance discussions hit the European coasts, Belgium developed a proper regulatory governance framework for autonomous state-owned enterprises, including specific checks and balances. The general commercial company code is applicable for the remaining issues. However, due to constitutional developments and divergent views on industrial policy, federal and regional Parliaments modified the applicable rules of a large number of SOE's, pushing the checks and balances to the edge. This paper assesses the 1991 corporate governance framework for Belgian autonomous SOE's, compares governance features of these entities and considers the differences with the commercial corporate governance practices. The paper starts with a brief introduction of the Belgian federal state and concludes with some thoughts for future developments.
Keywords: 330